Epidemiology of autoimmune encephalitis and comparison to infectious causes—Experience from a tertiary center - Yahel Segal; Ofer Rotschild; Yair Mina; Gadi Maayan Eshed; Tal Levinson; Yael Paran; Michal Dekel; Ronit Cohen‐Poradosu; Adi Ashkenazi; Itamar Moreno; Orna Aizenstein; Ora Halutz; et al. (Annals of Clinical and Translational Neurology)
Abstract Objectives The incidence of autoimmune encephalitis (AIE) has risen in the last decade, yet recent studies are lacking. We compared the epidemiology of autoimmune and infectious encephalitis cases in Tel‐Aviv Sourasky Medical Center (TASMC) between 2010 and 2020. Methods All encephalitis cases, aged 18 and above, admitted to TASMC between the years 2010 and 2020 were reviewed for demographic, clinical, laboratory, and imaging data and categorized based on etiology. Results Two hundred and twenty‐five patients with encephalitis were identified. The most common identifiable cause was viral (42%), followed by autoimmune encephalitis (35%), bacterial (18%), and fungal/parasitic (5%). The incidence of AIE cases out of the yearly admitted cases increased substantially, from 3.8/100 K in 2010 to 18.8/100 K in 2020. The incidence of viral cases also increased while those of bacterial and fungal/parasitic infections remained stable. Patients with AIE were younger compared to infectious patients (p‐value <0.001) and had lower markers of systemic and cerebrospinal fluid inflammation (p‐value for all <0.001). Seizures were more common among AIE patients (p‐value <0.001), yet one‐year mortality rates were higher among infectious patients (p‐value <0.001). Interpretation AIE incidence has risen significantly in our institution during the past decade, with current rates comparable to those of all infectious causes combined. Based on this cohort, clinical clues for an autoimmune etiology include a non‐inflammatory cerebrospinal fluid profile, the presence of seizures, and temporal lobe imaging abnormalities (also common in herpetic encephalitis). In light of its rising incidence and the importance of early treatment, AIE should be considered in the differential diagnosis of all encephalitis cases.